Meeting Students Where They Are - Brown,Nicole (2018)
The flexibility of the online classroom gives busy students around the world access to educational opportunities that have not been available in the past. These students are working hard in every aspect of their lives and with a little support from us, their online instructors, we can help them make the most of the time they have in order to learn and grow.
Keywords: Marketing